2013
DOI: 10.1128/aem.00721-13
|View full text |Cite
|
Sign up to set email alerts
|

Novel Rickettsiella Bacterium in the Leafhopper Orosius albicinctus (Hemiptera: Cicadellidae)

Abstract: Bacteria in the genus Rickettsiella (Coxiellaceae), which are mainly known as arthropod pathogens, are emerging as excellent models to study transitions between mutualism and pathogenicity. The current report characterizes a novel Rickettsiella found in the leafhopper Orosius albicinctus (Hemiptera: Cicadellidae), a major vector of phytoplasma diseases in Europe and Asia. Denaturing gradient gel electrophoresis (DGGE) and pyrosequencing were used to survey the main symbionts of O. albicinctus, revealing the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 44 publications
(42 reference statements)
1
23
0
Order By: Relevance
“…Spiroplasma as endosymbionts has been identified in Drosophila 39404142, ticks4344 and mosquitoes45. Diplorickettsia , Coxiella and Rickettsiella are obligate endosymbionts that have been identified in ticks28464748 and leafhoppers49. Here, we reported for the first time the presence of Spiroplasma and taxa related to Diplorickettsia and Rickettsiella in Ph.…”
Section: Discussionmentioning
confidence: 71%
“…Spiroplasma as endosymbionts has been identified in Drosophila 39404142, ticks4344 and mosquitoes45. Diplorickettsia , Coxiella and Rickettsiella are obligate endosymbionts that have been identified in ticks28464748 and leafhoppers49. Here, we reported for the first time the presence of Spiroplasma and taxa related to Diplorickettsia and Rickettsiella in Ph.…”
Section: Discussionmentioning
confidence: 71%
“…Pyrosequencing (454) yielded many more bacterial sequences than DGGE, as has been found in other studies of bacteria associated with sap sucking insects. For example, studies using DGGE or restriction fragment length polymorphism (RFLP) identified only three and four bacterial symbionts in the sweetpotato whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) and Pentastiridius leporinus (Hemiptera: Cixiidae), respectively [5,19], compared to studies using 454 pyrosequencing describing 13 and 21 bacterial genera associated with the brown planthopper Nilaparvata lugens (Hemiptera: Delphacidae) [68] and the leafhopper Orosius albicinctus (Hemiptera: Cicadellidae), respectively [33].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the recent sequencing of a Francisella-LE strain suggests that this symbiont has recently replaced a Coxiella-LE in at least one tick Clay et al 2008;Carpi et al 2011;Machado-Ferreira et al 2011;Almeida et al 2012;Lalzar et al 2012;Duron et al 2014aDuron et al , 2015a Obligate symbiont in most tick species Gottlieb et al 2015;Smith et al 2015b). Closely related to the agent of Q fever, Coxiella burnetii (Duron et al 2015a) 2 -Rickettsiella Scattered distribution in arthropods (Tsuchida et al 2010;Bouchon et al 2012;Iasur-Kruh et al 2013), common in ticks (Kurtti et al 2002;Vilcins et al 2009;Anstead & Chilton 2014;Duron et al 2015aDuron et al , 2016 Unknown effect in ticks. Facultative mutualist in aphids (Tsuchida et al 2010(Tsuchida et al , 2014Lukasik et al 2013a) and likely in other insects (Iasur-Kruh et al 2013).…”
Section: Introductionmentioning
confidence: 99%